Blood profiles among female undergraduate in Iraq after a 12-weeks home-based intervention program - Soh, Kim Geok; Noori, Jian Abdullah; Soh, Kim Lam; Japar, Salimah; Yusof, Aminuddin (Human Resource Management Academic Research Society, 2017)
The aim of this study is to investigate whether a 12-weeks home-based intervention program could improve blood profiles among female students in Iraq. A 12-week home-based intervention which consisted of physical activity and dietary awareness program was carried out at home. The subjects were 44 sedentary undergraduate female students from Soran University, Iraqi. Both experimental and control groups (n=22 in each group) completed practical tests at baseline pre-test, post-test1, and post-test2, but only the experimental group participants received the 12-weeks intervention program. The blood profiles measured were blood pressure, blood cholesterol, and blood glucose. Results showed that the experimental group demonstrated improvement in diastolic systolic blood pressure after undergone 6 weeks post-test intervention program. The reported f value was (F(2, 84)=-6.636, p=.047, η2=0.091). Significant blood profiles results were reported for diastolic blood pressure and blood glucose. However, the significant results were only reported after the subjects had undergone the 12-weeks intervention program. The reported f values were (F(2, 84)=-7.000, p=.007, ?2=0.163) and (F(2, 84)=-16.182, p=.003, η2=0.188), respectively. As the conclusion, a home-based physical activity and dietary intervention program can positively influence sedentary undergraduate female students’ blood profiles and the benefits can be achieved as early as after 6-weeks.